El campo médico argentino y su mirada al tribadismo, 1936-1955 - Ramacciotti, Karina Inés (2008)
This article describes and analyzes the discursive articulation on the lesbianism in the medical Argentine field between 1936 and 1955. The "truths" of the medicine possess a normative force which constitutes a suitable place to favor the heterosexual model and to impose this point of view to the rest of the society. First we will outline the medical arguments in the European area. They were the most accessed models by the medical Argentine elite. Then, we will analyze the re-readings and appropriations realized in Argentina, articulating them with the hegemonic heterosexual model of femininity.